The Use of Socio-Scientific Issues to Promote Prospective Biology Teachers’ Scientific Literacy and Research Skill Development - Haviz, M; Nasrul, Ervina; Azis, David; Maris, Ika Metiza; Wahyudi, Farhan (Universitas Negeri Semarang, 2024)
This study aims to investigate the use of SSI to promote prospective biology teachers’ scientific literacy and research skill development. This research uses quantitative methods with a true-experiment design. The treatments were Guided Inquiry (GI) and Research-based Learning (RbL) in two biology classes. This study involved 39 sixth-semester students, five males and 34 females. The lecturer applied the GI and RbL syntax at the 1-8th meetings to collect the data. At the 9-12th meeting, PBTs carried out guided work by studying articles containing themes or content of SSI from the scientific journal. Data analysis was carried out with descriptive statistics, and to differentiate between the two treatments, a test of equality of mean values was carried out using the t-test. This research provides several conclusions. First, SSI articles can be used as learning materials promoting scientific literacy and RSD-7. Second, using SSI with RbL and SSI with GI promotes prospective biology teachers’ scientific literacy. The SL components are explaining phenomena scientifically, evaluating and designing inquiry, interpreting data, and knowledge of scientific literacy. Third, using SSI with RbL and SSI with GI promotes prospective biology teachers’ RSD-7 skills at all levels: (1) Embark and Clarify, (2) Find and Generate, (3) Evaluate and Reflect, (4) Organize and Manage, (5) Analyze and Synthesize, and (6) Communicate and Apply. The seven levels in RSD-7 are prescribed research, bounded research, scaffolded research, self-initiated research, open research, adopted research, and enlarging research. There were no differences in RSD-7 skills between the SSI with RbL and GI treatments. Fourth, there is no difference in learning outcomes between the SSI with GI and RbL treatments.